1999
DOI: 10.1080/016502599383766
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Schooling and Occupation on Child-rearing Attitudes and Behaviours in Low Income Neighbourhoods in Cairo, Egypt

Abstract: As a developing country, Egypt and especially Cairo, is in a transitional phase between a traditional and a modern, education-based society and between traditional child-rearing values of passivity and obedience and new demands for academic competence. Education is seen by present day parents as the major vehicle for the future success and happiness of children and much effort is expended toward this goal. Thirty Cairene mothers from low income neighbourhoods with similar housing standards and crowding, but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
2
10
0
4
Order By: Relevance
“…Infants belonging to uneducated mothers had a higher risk of getting below average composite score than those belonging to highly educated mothers. This finding is in concurrence with previous studies, which reported that infants of less-educated mothers are more likely to be exposed to inadequate dietary intake, poorer sanitation [ 71 ] and receive less cognitive stimulation, than those of more-educated mothers [ 72 ]. In addition, the current results revealed that infants of housewives had a higher risk of getting below average socio-emotional composite score than infants of working mothers.…”
Section: Discussionsupporting
confidence: 92%
“…Infants belonging to uneducated mothers had a higher risk of getting below average composite score than those belonging to highly educated mothers. This finding is in concurrence with previous studies, which reported that infants of less-educated mothers are more likely to be exposed to inadequate dietary intake, poorer sanitation [ 71 ] and receive less cognitive stimulation, than those of more-educated mothers [ 72 ]. In addition, the current results revealed that infants of housewives had a higher risk of getting below average socio-emotional composite score than infants of working mothers.…”
Section: Discussionsupporting
confidence: 92%
“…In the present work, we also considered the relation between SES and parenting styles. Consistent with previous studies ( Bronfenbrenner, 1958 ; Chen et al, 1997 ; von der Lippe, 1999 ) parents with high educational levels were described as more authoritative than parents with low educational levels in Sweden, Italy and Greece. On the contrary, in our sample, parents with low educational levels were not perceived as more authoritarian than parents with high education levels.…”
Section: Discussionsupporting
confidence: 89%
“… Chen, Dong, and Zhou (1997) highlighted that parental occupation and education correlated positively with authoritative parenting for both parents, while they correlated negatively with authoritarian parenting for mothers. Additional evidence derives from von der Lippe’s (1999) study, which shows that less-educated mothers reported less authoritative parenting compared to more-educated mothers. More recently, Worden and Carlson (2005) , as well as Gracia and Herrero (2008) , suggested that the higher-educated parents are more likely to reject the acceptability of physical punishment of children.…”
mentioning
confidence: 99%
“…First, parenting style is related to social class: Working-class parents tend to have a less authoritative and more authoritarian parenting style than middle-class parents [25][26][27][28][29][30][31][32][33]. These social class differences may exist because working-class parents have less autonomy in their jobs, fewer financial resources, and more disorder in their neighborhoods.…”
Section: Parenting Stylementioning
confidence: 99%